Molecular Iodine: A Versatile Catalyst for the Synthesis of 2H-indazolo[2,1-b]phthalazine-1,6,11(13H)-trione Derivatives in Ethanol - Xiao Wang; Guangzhou Lu; Weiwei Ma; Liqzang Wu (E-Journal of Chemistry)
An efficient method for the synthesis of 2H-indazolo[2,1-b] phthalazine-1,6,11(13H)-trione derivatives by a three-component condensation reaction of dimedone, aromatic aldehydes and phthalhydrazide in the presence of a catalytic amount of molecular iodine in ethanol is described.